2008
DOI: 10.1002/adfm.200700407
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Morphological Modification on the Electrochemical Properties of SnO2 Nanomaterials

Abstract: The electrochemical performances of 1D SnO2 nanomaterials, nanotubes, nanowires, and nanopowders, are compared to define the most favorable morphology when SnO2 nanomaterials are adopted as the electrode material for lithium‐ion batteries. Changes in the morphology of SnO2 are closely related with its electrochemical performance. Some SnO2 nanomaterials feature not only an increased energy density but also enhanced Li+ transfer. The correlation between the morphological characteristics and the electrochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
180
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(192 citation statements)
references
References 25 publications
11
180
1
Order By: Relevance
“…The semicircle in the high-frequency region corresponds to the SEI film resistance (R f ), the semicircle in the medium-frequency region corresponds to the charge transfer impedance (R ct ), and the inclined line is related to the diffusion of Li + (Warburg impedance, W). [49] By fitting the equivalent circuit, as shown in the inset of Figure 3, the SEI film resistance and charge transfer resistance were calculated. Values for the SEI film resistance and the charge transfer resistance of 16.64 and 45.20 W cm 2 for the pristine Co 3 S 4 electrode and 7.58 and 25.66 W cm 2 for the Co 3 S 4 /G composite electrode, respectively, were determined.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…The semicircle in the high-frequency region corresponds to the SEI film resistance (R f ), the semicircle in the medium-frequency region corresponds to the charge transfer impedance (R ct ), and the inclined line is related to the diffusion of Li + (Warburg impedance, W). [49] By fitting the equivalent circuit, as shown in the inset of Figure 3, the SEI film resistance and charge transfer resistance were calculated. Values for the SEI film resistance and the charge transfer resistance of 16.64 and 45.20 W cm 2 for the pristine Co 3 S 4 electrode and 7.58 and 25.66 W cm 2 for the Co 3 S 4 /G composite electrode, respectively, were determined.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[20][21][22][23] Lou reported that 6-10 nm SnO 2 /C nanoparticles with 8% carbon can deliver an initial capacity of 1100 mAh g −1 , and this material retained a capacity as high as 631 mAh g −1 after 100 cycles. [23] Zhang et al developed a strategy in which SnO 2 nanoparticles were uniformly loaded onto cross-stacked carbon nanotube sheets, an approach which exhibited impoved performance.…”
Section: Introductionmentioning
confidence: 98%
“…[24,25] As shown in Figure 5, the discharge capacity drops from 1771.0 to 721.1 mAh g À1 after the first cycle. The specific capacity of the SnO 2 film for selected cycles is 1771.0 (1st), 721.1 (2nd), 483.9 (10th), 394.0 (20th), and 292.2 (50th).…”
mentioning
confidence: 91%
“…This means that the SnO 2 film has an initial coulombic efficiency of 47.7 %, which is higher than that of the pure nanopowder SnO 2 that we have reported previously. [24] The capacity loss of SnO 2 is mainly attributed to the formation of the solid-electrolyte interphase (SEI) layer and the volume variation of Sn during cycling, which leads to capacity degradation of the anode. For the as-prepared SnO 2 thin film, the improvement in the electrochemical behaviour can be attributed to the 3D reticular structure, which can accommodate the volume changes of Sn particles during charging and discharging.…”
mentioning
confidence: 99%